Cortisol reactivity, maternal sensitivity, and infant preference for mother's familiar face and rhyme in 6-month-old infants. - Thompson LA; Trevathan WR (Journal of Reproductive & Infant Psychology, 2009)
This study investigated how cortisol (stress) reactivity and mothers' behavioural sensitivity affect familiarity preferences in 6-month-old infants. Relations between sensitivity and stress were explored using saliva samples taken from mothers and infants before, and 20 min after, two preferential looking experiments. Photographs and voice recordings from infants' mothers were incorporated into standard visual preference tasks. Sensitivity was assessed by determining the degree of behavioural synchrony between mother and infant from a 10-min interaction period preceding the preferential looking experiments. Results showed that decreasing infant cortisol reactivity and greater maternal sensitivity were associated with familiarity preferences for mother's face stimuli. For the experiment with voice stimuli, a sex difference was obtained in the relationship between the directionality of cortisol reactivity and familiarity preferences. Results are related to a parallel study with 3-month-old infants, and issues are discussed in terms of infants' developing emotional independence from mother.